Tanggung Jawab Direksi Atas Pelanggaran Fiduciaryduty Yang Mengakibatkan Perseroan Pailit - Mira Indrawati; Abdul Manan; Dhoni Martien (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The board of directors' responsibilities for breaches of fiduciary duty that resulted in the company's bankruptcy are discussed. The approach method used in this legal research is a normative juridical approach that is backed up by empirical juridical evidence in the form of a detailed description, namely deductive research that begins with an analysis of the articles in the applicable laws and regulations governing the legal consequences for board of directors violations of fiduciary duty. Thus, the company becomes bankrupt, and the board of directors is responsible for violating the fiduciary duty and causing the company to become bankrupt. The Board of Directors, as a corporate organ, is obligated to act in the best interests of the corporation, not of the shareholders acting in their capacity as directors. In general, the board of directors must consider the interests of shareholders and other stakeholders when performing their duties as directors. In general, the board of directors must consider the interests of the corporation's shareholders and stakeholders. The Company Law regulates the directors' liability for losses or bankruptcy suffered by the company as a result of their actions.Keywords: Board of Director’s responsibility; Fiduciary duty; Bankruptcy Abstrak:Pembahasan tanggung jawab direksi atas pelanggaran fiduciary duty yang mengakibatkan perseroan pailit. Metode pendekatan yang dipergunakan dalam penelitian hukum ini adalah metode pendekatan yuridis normatif yang didukung dengan yuridis empiris dengan merinci uraian yaitu suatu penelitian yang secara deduktif dimulai analisa terhadap pasal-pasal dalam peraturan perundang- undangan yang mengatur terhadap permasalahan akibat hukum atas pelanggaran fiduciary duty oleh direksi, sehingga menyebabkan perseroan pailit serta tanggung jawab direksi yang melanggar fiduciary duty dan menyebabkan perseroan tersebut pailit. Direksi sebagai organ dari perseroan yang memiliki kewajiban menjalankan fiduciary duty terhadap korporasi, bukan terhadap pemegang saham menjalankan fungsinya sebagai direksi. Secara umum direksi juga harus memperhatikan kepentingan shareholder dan para stakeholder dari korporasi, dalam menjalankan fungsinya sebagai direksi. Secara umum  direksi juga harus memperhatikan kepentingan shareholder dan para stakeholder dari korporasi. UUPT mengatur tentang tanggung jawab Direksi perseroan atas kerugian atau kepailitan yang dialami perseroan yang dikarenakan perbuatan Direksi.Kata Kunci: Tanggungjawab Direksi; Fiduciary duty; Pailit